Family and cultural factors impacting entrepreneurship in war time Lebanon - Fahed-Sreih, Josiane (2010)
This study profiles the characteristics, attributes and growth orientations of Lebanese entrepreneurs including the relationships, roles and contributions that family and culture play in the development of private SMEs. Drawing on a sample of 112 entrepreneurs' psychographic motives, demographic attributes and business activities are revealed. Family and enterprise relationships related to employment, investment and active family participation and growth orientations are empirically tested. The findings suggest that entrepreneurs are motivated by the need for independence and flexibility. Entrepreneurs were found to rely heavily on family member participation to establish, develop and grow their enterprises.